2017
DOI: 10.1002/adbi.201700067
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts on Scaffolds

Abstract: Scaffolds are instrumental in the engineering of functional tissues, and therefore have been an intense area of interest within regenerative biology and medicine in areas of research and development. Many approaches exist for creating scaffolds with either natural or synthetic advanced materials, which are subsequently coupled with cells and other materials and microintegrated with the aid of a bioreactor, finally forming a functional three‐dimensional tissue. Although many advances have been made over the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 125 publications
(79 reference statements)
0
7
0
1
Order By: Relevance
“…[12] Similarly, emerging techniques such as cell electrospinning are not compatible with melt electrospinning. [13]…”
Section: Introductionmentioning
confidence: 99%
“…[12] Similarly, emerging techniques such as cell electrospinning are not compatible with melt electrospinning. [13]…”
Section: Introductionmentioning
confidence: 99%
“…Significant challenges exist in the development of any acellular bioresorbable tissue scaffold manufacturing technology [2,6,7]. Techniques that obtain scaffolds via the decellularisation of biological tissue (porcine, bovine, or human) [8,9,10] can result in tissues closely resembling the original tissues, and can have specific biological interactions with cells that are difficult to duplicate synthetically.…”
Section: Resultsmentioning
confidence: 99%
“…Layering sub-micrometer-sized fibers over each other resulted in structures with different grid sizes ( Figure 6C) up to a height of 1 mm. [177] Adv. [88] In vitro cell culture studies showed good adhesion, growth, and differentiation of primary human mesenchymal stromal cells (hMSCs), human periodontal ligament (hPDL), and mesenchymal precursor cells ( Figure 6B).…”
Section: Toward 3d Electrojettingmentioning
confidence: 99%
“…[175,176] Additionally, cells cannot be directly printed using melt electrospinning. [177] Adv. Mater.…”
Section: Toward 3d Electrojettingmentioning
confidence: 99%